2016
DOI: 10.1186/s12884-016-1168-5
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of birth outcomes at the Mother and Child Health Hospital in Lao People’s Democratic Republic, 2004–2013

Abstract: BackgroundThe Lao People’s Democratic Republic (Lao PDR) is a lower-middle income country making steady progress improving maternal and child health outcomes. We sought to ascertain if there have been improvements in three specific birth outcomes (low birth weight, preterm birth and small for gestational age) over the last decade.MethodsWe retrospectively reviewed birth records between 2004 and 2013 at the Mother and Child Health (MCH) hospital in Vientiane. We defined preterm birth as gestation <37 weeks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In this study as reported in other LMICs, participants reported poor record-keeping and an absence of an annual audit [ 4 , 6 , 7 ]. A review of data in the Mother and Child Health hospital in Vientiane found while all deliveries should be recorded into a hard-copy logbook, logbooks were not always available and date of birth often limited to year of birth [ 21 ]. Our research also affirms other studies which suggest there is often confusion among healthcare providers regarding the classification of stillbirth [ 4 , 6 , 7 , 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study as reported in other LMICs, participants reported poor record-keeping and an absence of an annual audit [ 4 , 6 , 7 ]. A review of data in the Mother and Child Health hospital in Vientiane found while all deliveries should be recorded into a hard-copy logbook, logbooks were not always available and date of birth often limited to year of birth [ 21 ]. Our research also affirms other studies which suggest there is often confusion among healthcare providers regarding the classification of stillbirth [ 4 , 6 , 7 , 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review of data in the Mother and Child Health hospital in Vientiane found while all deliveries should be recorded into a hard-copy logbook, logbooks were not always available and date of birth often limited to year of birth [ 21 ]. Our research also affirms other studies which suggest there is often confusion among healthcare providers regarding the classification of stillbirth [ 4 , 6 , 7 , 21 23 ]. Another study in Lao PDR of five hospitals examined the causes and incidences of neonatal diseases and deaths also found inconsistency in documentation, a lack of differentiation between stillbirths with maceration and intrapartum stillbirths and the potential for some neonatal deaths to have been misclassified as stillbirth [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies found no risk factors associated with HBV infection status (37), others have identified significant associations. HBsAg prevalence among blood donors was higher in males and increased significantly with age (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…The declining of premature birth and asphyxia might be due to the successful policy of Health Strategic Plan 2008-2015, which comprised: optimization of primary healthcare; health services accessibility; empowering human resources to handle maternal, neonatal, child health, degenerative diseases; and the distribution for health care workers that focus on nine priority health sector reform (16,17). The number of death due to birth asphyxia and premature birth in Laos were caused by maternal knowledge especially about safe pregnancy, nutritional support during pregnancy, and singleton pregnancy (34). The decreasing NMR in Laos was associated with the health policy that focused on free services for antenatal care, postnatal care, and delivery services.…”
Section: Discussionmentioning
confidence: 99%